The last letter from your lover - Moyes, Jojo, 1969- (Penguin Books, 2012)
In 1960, Jennifer Stirling wakes in the hospital and remembers nothing--not the car accident that put her there, not her wealthy husband, not even her own name. Searching for clues, she finds an impassioned letter, signed simply "B," from a man for whom she seemed willing to risk everything. In 2003, journalist Ellie Haworth stumbles upon the letter and becomes obsessed with learning the unknown lovers' fate--hoping it will inspire her own happy ending.